Effectiveness of one-to-one feedback methods of teaching with proper metered-dose inhaler technique and correcting errors in chronic obstructive lung disease patients - Özkan Çiğdem Gamze; Kaşikçi Mağfiret (Sciendo, 2023)
To determine the most common mistakes made during the use of a metered-dose inhaler (MDI), and the effect of the repeated trainings performed with demonstration method by providing one-to-one feedback on these mistakes.